Circulating cytokines in patients with cat scratch disease - Papadopoulos, N. G.; Gourgiotis, D.; Bossios, A.; Fretzayas, A.; Moustaki, M.; Karpathios, T. (Clin Infect Dis, 2001)
Levels of circulating interleukin (IL)-2, IL-6, and IL-10, measured by enzyme-linked immunosorbent assay, were significantly higher in patients with cat scratch disease (CSD) than in healthy control subjects; no induction of IL-12 was observed, and levels of interferon-gamma and IL-4 were generally not detectable. This is the first report showing increased circulating cytokine levels in patients with CSD. The induction of these mediators can partly explain some clinical and pathological features of the disease.
Keywords: Antibodies; Bacterial Bartonella henselae Case-Control Studies Cat-Scratch Disease Child Cytokines Female Humans Immunity; Cellular Interferon-gamma Interleukin-10 Interleukin-12 Interleukin-2 Interleukin-4 Interleukin-6 Male